2009
DOI: 10.1007/978-3-642-05082-4_9
|View full text |Cite
|
Sign up to set email alerts
|

On the Ostensibly Silent ‘W’ in OWL 2 RL

Abstract: Abstract. In this paper, we discuss the draft OWL 2 RL profile from the perspective of applying the constituent rules over Web data. In particular, borrowing from previous work, we discuss (i) optimisations based on a separation of terminological data from assertional data and (ii) the application of authoritative analysis to constrain third party interference with popular ontology terms. We also provide discussion relating to the applicability of new OWL 2 constructs for two popular Semantic Web ontologies -n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…For the purposes of this paper, we chose to focus on a materialization approach, although supporting resolution-based reasoning is considered future work. We note that many Semantic Web rule-based reasoners, including DLEJena [36], SAOR [23], OwlOntDb [16] and RuQAR [5], also follow a materialization approach.…”
Section: Reasoning Tasksmentioning
confidence: 99%
“…For the purposes of this paper, we chose to focus on a materialization approach, although supporting resolution-based reasoning is considered future work. We note that many Semantic Web rule-based reasoners, including DLEJena [36], SAOR [23], OwlOntDb [16] and RuQAR [5], also follow a materialization approach.…”
Section: Reasoning Tasksmentioning
confidence: 99%
“…: OWL 2 RL [51]. In [73], we presented discussion on the new ruleset from the perspective of application over Web data, and showed that the ruleset is not immediately amenable to the requirements outlined, and still needs amendment for our purposes.…”
Section: High-level Approachmentioning
confidence: 99%
“…Herein, we follow on from discussion in [73] and implement a fragment of OWL 2 RL/RDF: we present our ruleset in Appendix B and now briefly discuss how we tailored the standard ruleset [51] for our purposes. 37 Firstly, we do not apply rules which specifically infer what we term as "tautological statements", which refer to syntactic RDFS and OWL statements such as rdf:type rdfs:Resource statements, and reflexive owl:sameAs statements -statements which apply to every term in the graph.…”
Section: High-level Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Please note that we do not consider rules which infer an inconsistent (have a false consequent), and consider equality reasoning separately in the consolidation component: thus we do not support any of the rules in rule group R2 as defined in [73] -also of note, we co-incidently do not supported any rules which use the new OWL 2 constructs, since they require A-Box joins which -as we will justify herein -our system currently does not support. 38 For example, we consider the triples mo:wikipedia rdfs:subPropertyOf foaf:page .…”
Section: High-level Approachmentioning
confidence: 99%